2017
DOI: 10.1097/inf.0000000000001771
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the QuantiFERON TB Gold In-tube Assay With Tuberculin Skin Test for the Diagnosis of Latent Tuberculosis Infection Among HIV-infected and Uninfected Children

Abstract: A moderate correlation exists between TST and QTF-GIT among HIV-infected and uninfected children with preserved immune function in an area of moderate tuberculosis endemicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…A meta-analysis found that the sensitivity of ELISPOT (72%, 95 CI 62–81%) was higher than that of ELISA (61%, 95 CI 41–75%) in this population [ 57 ]. Overall, the concordance between IGRAs and the TST is medium or poor [ 66 , 67 ]. Concordance is worse in low-income countries and patients with a low level of CD4 + T-cells [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis found that the sensitivity of ELISPOT (72%, 95 CI 62–81%) was higher than that of ELISA (61%, 95 CI 41–75%) in this population [ 57 ]. Overall, the concordance between IGRAs and the TST is medium or poor [ 66 , 67 ]. Concordance is worse in low-income countries and patients with a low level of CD4 + T-cells [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The test’s veracity depends on the generation of an appropriate standard curve, which must cover the specific criteria established by the test. A positive result is considered when the amount of IFN- γ released in response to antigens ESAT-6, CFP 10 and TB 7.7 has a value greater than 0.35 IU/ml, according to the manufacturer’s instructions [ 11 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…This test detects the amount of interferon gamma (IFN-γ) released by lymphocytes in the blood of sensitized people, using the Enzyme-Linked Immunosorbent Assay (ELISA). It contains mixtures of synthetic peptides similar to those presented by MTB and absent in the Bacillus Calmette Guerin (BCG) used for vaccination: white secretory early antigen (ESAT-6), culture-filtered protein (CFP-10) [ 9 , 10 ] and in later years the TB 7.7, which reduces the number of indeterminate results and increases the diagnostic sensitivity and specificity [ 11 13 ]. Recently, to improve the sensitivity of the QFT-GIT in young children, or people with recent exposure, or with HIV infection, was developed the QFT-Plus that has one additional tube for the induction of cell-mediated immune responses from both CD4+ 31 and CD8+ T cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The QFT-GIT has been reported to have higher sensitivity, specificity and be more attractive than the tuberculin skin test (TST) [4][5][6][7][9][10][11] which may result in interpretation errors [5,6,11], including the need of two clinic visits. Collecting blood samples may not frequently encounter difficulties compared with other specimens collection and QFT-GIT can provide rapid results, within two days [6].…”
Section: Introductionmentioning
confidence: 99%